MUTU PENDIDIKAN DALAM PERSPEKTIF ISLAM - Adha, Nurul (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
This paper examines the quality of education from an Islamic perspective, emphasizing a balanced development of students’ intellectual, moral, spiritual, and social aspects. The study addresses how Islamic education can shape a generation that is knowledgeable, faithful, and morally upright while being able to face the challenges of globalization, technological advancement, and socio-cultural changes. The purpose of this study is to explain the concepts, standards, and challenges of Islamic education quality to ensure its effective implementation in the modern era, producing academically competent and strong-charactered students. This study uses a literature review approach, systematically analyzing relevant literature, policy documents, and Islamic educational practices to identify principles, supporting factors, and implementation challenges. The findings indicate that the quality of Islamic education is measured not only by academic achievement but also by the success in cultivating moral character, social skills, and positive societal contributions. The implementation of a Qur’an- and Hadith-based curriculum, professional teacher quality, and a conducive Islamic learning environment are key factors in enhancing education quality, keeping it relevant, character-driven, and able to prepare a competitive future generation